2020
DOI: 10.3390/ijerph17197185
|View full text |Cite
|
Sign up to set email alerts
|

Digital Healthy Diet Literacy and Self-Perceived Eating Behavior Change during COVID-19 Pandemic among Undergraduate Nursing and Medical Students: A Rapid Online Survey

Abstract: Assessing healthy diet literacy and eating behaviors is critical for identifying appropriate public health responses to the COVID-19 pandemic. We examined the psychometric properties of digital healthy diet literacy (DDL) and its association with eating behavior changes during the COVID-19 pandemic among nursing and medical students. We conducted a cross-sectional study from 7 April to 31 May 2020 at 10 public universities in Vietnam, in which 7616 undergraduate students aged 19–27 completed an online survey t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(95 citation statements)
references
References 57 publications
2
87
1
5
Order By: Relevance
“…This could be further explained by the fact that higher HL and eHEALS scores were associated with healthier eating and physical activity behaviors in this study. In a previous study, we also found that medical and nursing students with higher digital healthy diet literacy had healthier eating behaviors during the pandemic [82]. In addition, eHealth literacy was found to be associated with key issues related to seeking out exercise regime information and maintaining a healthy diet [83].…”
Section: Principal Findingsmentioning
confidence: 68%
“…This could be further explained by the fact that higher HL and eHEALS scores were associated with healthier eating and physical activity behaviors in this study. In a previous study, we also found that medical and nursing students with higher digital healthy diet literacy had healthier eating behaviors during the pandemic [82]. In addition, eHealth literacy was found to be associated with key issues related to seeking out exercise regime information and maintaining a healthy diet [83].…”
Section: Principal Findingsmentioning
confidence: 68%
“…As of recently, more studies have been published on COVID-19 lockdown effects on dietary habits, as well as on other lifestyle behaviors [ 5 , 6 , 7 , 17 , 18 ]. However, most of the previous studies focused on adult population, and only few studies have been published so far about COVID-19 lockdown influence on lifestyle change in adolescents [ 19 , 20 , 21 ] and in medical students [ 22 , 23 ]. Hence, we aimed to investigate dietary habits and other related lifestyle behaviors changes in adolescents and medical students resulting to COVID-19 lockdown in Croatia.…”
Section: Introductionmentioning
confidence: 99%
“…In this direction, applied studies in university students have shown that psychometric instruments' validation allows an adequate evaluation of eating behavior and lifestyle. (16,17) COVID-19 confinement and measures of its containment have an evident impact on the population's lifestyle-related behavior. (18) This situation is critical considering the current obesity epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire demonstrated adequate validity and reliability in university students, like some recent studies that showed high confidence and validity to analyze eating behavior and lifestyle during confinement by Covid-19 in university students. (17,20) This questionnaire is a short, concise, and user-friendly tool possible to be completed in 10 to15 min, avoiding respondents' lack of patience and, consequently, inaccuracy in the assessment. It consists of four dimensions covering all critical information required to assess the participants' eating habits (intake, meal pattern, and snack consumption) and lifestyles (exercises, tobacco, and alcohol).…”
Section: Discussionmentioning
confidence: 99%